2010
DOI: 10.4088/jcp.09r05786blu
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Reuptake Inhibitor Antidepressants and Abnormal Bleeding

Abstract: On the basis of the findings of our literature search, we suggest that SSRI-induced increase in gastric acid secretion may explain the GI bleeding risk and that SSRI-related effects on platelet reactivity, endothelial reactivity, and inflammatory markers may explain the ischemic heart disease protective effect. Because the absolute risk of GI bleeds with SSRIs is low, precautions are probably necessary only in high-risk patients, such as those with acid-peptic disease and those with a history of bleeds. We dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 258 publications
(82 citation statements)
references
References 58 publications
2
79
0
1
Order By: Relevance
“…25,26 Next, depression is associated with an increased risk of ischemic heart disease events, 27 and NSAIDs may further increase this risk. For example, a meta-analysis of 25 studies showed that most of the commonly used NSAIDs were associated with a dosedependent increase in the risk of myocardial infarction 28 ; some NSAIDs may additionally increase the risk of stroke.…”
Section: Nsaids and Medical Risksmentioning
confidence: 99%
“…25,26 Next, depression is associated with an increased risk of ischemic heart disease events, 27 and NSAIDs may further increase this risk. For example, a meta-analysis of 25 studies showed that most of the commonly used NSAIDs were associated with a dosedependent increase in the risk of myocardial infarction 28 ; some NSAIDs may additionally increase the risk of stroke.…”
Section: Nsaids and Medical Risksmentioning
confidence: 99%
“…Apart from the effect on serotonin in platelets, other mechanisms responsible for increased bleeding risk in patients on SSRI treatment have been discussed [14]. For example, the increased gastrointestinal bleeding risk may be caused by enhanced gastric acid secretion (due to SSRI use) rather than the influence of thrombocyte aggregation.…”
Section: Figmentioning
confidence: 99%
“…Inhibition of serotonin transporters is one of them [40]. Platelets release serotonin at sites of bleeding and vascular damage; however, they do not synthesize serotonin themselves and acquire it from the blood and store it [40,41]. Because of inhibition of serotonin transport and uptake, SSRIs may also worsen the bleeding caused by ASA and clopidogrel [40,41].…”
Section: Drugs and Gastric Damagementioning
confidence: 99%
“…There are few possible mechanisms responsible for this effect. Inhibition of serotonin transporters is one of them [40]. Platelets release serotonin at sites of bleeding and vascular damage; however, they do not synthesize serotonin themselves and acquire it from the blood and store it [40,41].…”
Section: Drugs and Gastric Damagementioning
confidence: 99%